Requiem for the Term ‘Carcinoid Tumour’ in the Gastrointestinal Tract? - Runjan Chetty (Canadian Journal of Gastroenterology)
Use of the term ‘carcinoid tumour’ to describe a unique type of tumour in the gastroenteropancreatic system is endemic in the medical literature and in daily clinical and pathological parlance. However, it is a somewhat misleading moniker because a spectrum of histopathological changes and hence, biological outcomes may occur in these tumours. The World Health Organization classification scheme recommends the use of the terms neuroendocrine tumours or carcinomas, which may be stratified as well-differentiated neuroendocrine tumours with benign or uncertain behaviour, well-differentiated tumours with low-grade neuroendocrine carcinoma behaviour and high-grade neuroendocrine carcinomas. These categories may be applied within different sites in the gastrointestinal tract and pancreas, and convey a sense of biological behaviour. In addition, a recently suggested tumour-node-metastasis scheme has been proposed and awaits clinical validation and acceptance. Thus, the term ‘carcinoid’ has served its purpose well, but its use should be phased out in favour of ‘neuroendocrine tumour’ or ‘neuroendocrine carcinoma’.